ASSOCIATION OF GENERATION TIME WITH ANTI-TUBERCULAR DRUG(S) RESISTANCE PATTERN OF MYCOBACTERIUM TUBERCULOSIS ISOLATES AMONG TREATMENT FAILURE PULMONARY TUBERCULOSIS PATIENTS - Goswami, Avranil; Chakraborty, Urmita; Bhattacharya, Basudev; Pal, Nishith Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The emergence of drug resistance has complicated tuberculosis (TB) scenario and is associated to treatment failure. The causative agent, Mycobacterium tuberculosis is usually slow growing and has been implicated as a contributing factor for drug tolerance and development of resistant strains. On the other hand, if rapidly growing bacilli, with shorter generation time emerge, mutations may lead to the development of drug resistance. From the hypothesis, this study was aimed to explore the whether there is any association between the generation time of Mycobacteria with their distinct drug resistant pattern. Methods: In-vitro generation time was determined from 77 mycobacterial isolates with varied drug resistance pattern, i.e. rifampicin resistant (RIFR), isoniazid resistant, multi-drug resistant (MDR), the sensitive clinical strains along with reference strains. The minimal inhibitory concentration was also determined for the respective resistant groups. Results: Among the individual group of clinical isolates, there was a significant negative association between generation time and drug resistance pattern of RIFR isolates. Conclusion: Keeping the current upsurge of the MDR-TB epidemic in India and the influence of generation time on dosing schedule and treatment strategy, necessary customization of dosing and therapeutic planning seemed urgent to minimize the operational and clinical potential for development of drug resistance among treatment failure pulmonary TB patients in this country. Keywords: Mycobacterium tuberculosis, Generation time, Multi-drug resistant, Treatment failure.